Avaliação da eficácia de um treinamento on-line para cuidadores informais de idosos com doença de Alzheimer: ensaio clínico controlado randomizado - Alves, Ludmyla Caroline de Souza (2020)
Introduction: The increase in older adults diagnosed with Alzheimer's disease (AD) brings challenges to society as a whole, especially to family members, who often become informal caregivers for these individuals. The lack of information or training can negatively impact the caregiver-patient relationship. Several types of interventions aimed at caregivers are created, with the objective of informing about the disease, reducing overload, depressive and anxious symptoms, among others. As an example of intervention we can mention on-line interventions, based on programs and websites. Objective: To evaluate the effectiveness of on-line training through the website of the Brazilian Alzheimer's Association (ABRAZ) in informal caregivers of older adults with AD. Method: This is a randomized controlled clinical trial. They were evaluated by means of a protocol composed of the instruments: Zarit Overload Scale, Center Epidemiological Studies for Depression - CES –D, Hospital Anxiety and Depression Scale - HADS, Memory Complaint Scale- NDE, Dementia Knowledge Assessment Tool Version Two - DKAT-2 and EuroQol 5 Dimensions- EQ 5d, 30 informal caregivers of individuals with AD, randomly divided into two groups: intervention (IG) and control (CG). The IG accessed the ABRAZ website and received information on defined topics, and the GC received printed material with basic information. The intervention lasted three months and the caregivers were reassessed after that period, using the same instruments. Results: The profile of caregivers was defined by: 86.7% women in both groups, and an average education of 13.3 years for both. In addition, 66% of the caregivers of the IG and 60% of the CG didn’t live with the elderly. It was observed that after the intervention there were significant differences between the groups regarding depressive and anxious symptoms. There was a positive correlation between overload and anxiety symptoms (r = 0.399; p≤0.05), in addition to overload and stress (0.491; p≤0.01) and depression (0.685; p≤0.01). Health status showed an inverse correlation with stress (r = -0.381; p≤0.05) and memory complaints (r = -0.426; p≤0.05). Data Analysis: Spearman and Pearson correlation tests, and Anova comparison tests (Oneway) of the averages of the measurement instruments were applied before and after the intervention for independent samples according to the distribution. The SPSS 23.0 software was used for data analysis. P-values ≤ 0.05 were considered significant. Conclusions: The intervention produced effects on anxious and depressive symptoms for the intervention group, but it didn’t increase the knowledge of caregivers regarding dementia, as supposed.